BUILDING A STRONG COMMUNICATION CULTURE: THE KEY TO ORGANIZATIONAL SUCCESS - Iin Yatrin Hanariyah (Sean Institute, 2023)
This research aims to explore and analyze the factors that contribute to the formation of a strong communication culture in an organizational context, as well as identifying the keys to success related to this strong communication culture. This research uses a qualitative approach with descriptive methods. The research results show that factors include mobility, economic interdependence, developments in information and communication technology, immigration patterns, and political prosperity. All of these factors have a significant impact on the way individuals and organizations communicate in an increasingly global and multicultural environment. Furthermore, to build a strong communication culture, you can do this by carrying out direct communication to understand non-verbal expressions, being a good listener to understand the perspectives and needs of colleagues, providing honest and constructive feedback to guide and motivate team members, respecting different opinions and managing differences with respect, being friendly and welcoming to create a positive work atmosphere, conveying messages clearly and easily understood and being open and accepting feedback with an open attitude